2019
DOI: 10.18203/2320-6012.ijrms20191631
|View full text |Cite
|
Sign up to set email alerts
|

External validation of Tzanakis scoring system in acute appendicitis in a rural hospital

Abstract: Background: Acute appendicitis is one of the most common cause of acute abdomen surgery. Several scoring systems have been adopted by physicians to aid in the diagnosis and decrease the negative appendicectomy rate. Tzanakis scoring system is one such score. Objective of present study was the validation of this scoring system in our population and compare its accuracy with histopathological examination (HPE).Methods: A retrospective study was carried out at the Department of Surgery at Mohammad Afzal Beigh Mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…6,7 In a recent study done in Pakistan, its sensitivity, specificity and overall diagnostic score was determined to be 99%, 91% and 95% respectively 8 indicating that it to be an accurate modality for - ----------------------------------------------------------------------------------------Received on 15-06-2021 Accepted on 25-10-2021 diagnosing of acute appendicitis and preventing a negative laparotomy in this region of the world. 9 However, a prospective study done in 2019 in India concluded that Tzanaki score is considering better diagnostic scoring system than Alvarado score for acute appendicitis 10 .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In a recent study done in Pakistan, its sensitivity, specificity and overall diagnostic score was determined to be 99%, 91% and 95% respectively 8 indicating that it to be an accurate modality for - ----------------------------------------------------------------------------------------Received on 15-06-2021 Accepted on 25-10-2021 diagnosing of acute appendicitis and preventing a negative laparotomy in this region of the world. 9 However, a prospective study done in 2019 in India concluded that Tzanaki score is considering better diagnostic scoring system than Alvarado score for acute appendicitis 10 .…”
Section: Introductionmentioning
confidence: 99%